CULTURAL INTERACTIONS AND THE SOCIO-RELIGIOUS TRANSFORMATION AMONG THE TRIBALS OF BASTAR - Manickam, Thomas (Journal of Dharma, 1992)
Bastar, the largest tribal district of Madhyapradesh, probably of the whole of India, accommodates about two million tribal people. The prominent among them are the Madias, the Ghonds, the Bhils, the Oraons and their clannish groups. By and large each tribal community occupies its own aboriginal geographical boundaries with their respective tribal traditions and customs, dialects, administrative systems, social celebrations, religious beliefs, myths, folklores, ballard songs, moral and ritual practices, including superstitions. Ancestral and cultural identity is being scrupulously maintained in all possible ways and it is one of the primary concerns of each tribe. Wilful violations by any inmate of a clan of a tribe of its ancestral beliefs and practices would end up in estracisation together with physical tortures and social censures and sanctions. Yet the urge on the part of the younger generations to accommodate to the demands of contemporary cultural interations of other peoples is conspicuous and the tension and the strain is significant. In this context it is proper to make some critical observations on the phenomenon of the socio-religious transformation, taking place among the tribals of Bastar.